More practical experiments in physics - Khatri, Vikas (New Delhi : MG Books, 2020)
A book of practical work of learning that is to develop students' general and specific skills to carry out scientific experiments, and to enhance their practical competence in handling experimental instrumentations.
Keywords: Study and teaching. -